The Acquisition of Arabic Grammar as a Second Language among Arabic Learners at King Saud University - Azzam, Abdullah Fahri Azzam (Journal of Arabic Language Studies and Teaching, 2022)
This study dealt with the acquisition of Arabic grammar by several learners of Arabic as a second language at the Institute of Arabic Linguistics at King Saud University in Riyadh, where the students faced some difficulties in applying Arabic grammar. This study focused on five topics of Arabic grammar, including definitive and In-definitive words, Singular, Duality and Plural. By conducting a measurement test on 24 students at the Institute of Arabic Linguistics from 3 different levels, from which the researcher aims to know their cognitive growth in that grammar and know the factors affecting these grammatical chapters and suggest some appropriate solutions related to these grammatical chapters. After conducting a test and correcting the students' answers, it was found that distance learning did not hurt the acquisition of these grammatical chapters. It was also found that the presence of the dual form in the student's mother language does not necessarily mean the acquisition of these grammatical chapters faster. It was also found that the students' linguistic adequacy in these grammatical chapters is gradually growing. تناولت هذه الدراسة على اكتساب قواعد اللغة العربية لدى متعلمي اللغة العربية لغة ثانية في معهد اللغويات العربية بجامعة الملك سعود بمدينة الرياض، حيث واجه الطلاب بعض صعوبات في تطبيق قواعد اللغة العربية. وقد ركز هذه الدراسة على خمسة موضوعات من قواعد اللغة العربية من التعريف والتنكير، والإفراد، والتثنية والجمع. وذلك بإجراء اختبار قياس على 24 طالبا من طلاب معهد اللغويات العربية من 3 مستويات مختلفة ليستهدف منه الباحث معرفة النمو المعرفي عندهم في تلك الأبواب النحوية، ومعرفة العوامل المؤثرة في اكتسابها، واقتراح بعض الحلول المناسبة حتى تساعد الطلاب في اكتسابها. وتبين بعد إجراء اختبار، وتصحيح إجابات الطلاب بأن تعليم عن بعد لم يؤثر تأثيرا سلبيا كليا في اكتساب هذه الأبواب النحوية، وتبين أيضا بأن وجود صيغة المثنى في لغة الطالب الأم لا يعني بالضرورة اكتساب هذه الأبواب النحوية بشكل أسرع. وتبين أيضا بأن كفاية الطلاب اللغوية في هذه الأبواب النحوية ينمو نموا تدريجيا.